A transgenic male-only strain of the New World screwworm for an improved control program using the sterile insect technique. Issue 1 (December 2016) - Concha, Carolina; Palavesam, Azhahianambi; Guerrero, Felix; Sagel, Agustin; Li, Fang; Osborne, Jason; Hernandez, Yillian; Pardo, Trinidad; Quintero, Gladys; Vasquez, Mario; Keller, Gwen; Phillips, Pamela; et al.
Abstract Background The New World screwworm, Cochliomyia hominivorax, is a devastating pest of livestock endemic to subtropical and tropical regions of the Western hemisphere. The larvae of this species feed on the tissue of living animals, including man, and can cause death if untreated. Over 60 years ago, the sterile insect technique (SIT) was developed with the aim of eradicating this pest, initially from Florida but subsequently from all of North and Central America. From the outset it was appreciated that SIT would be more efficient if only sterile males were released in the field, but this was not possible until now. Results Here, we report on the development and evaluation of the first sexing strains ofC. hominivorax that produce only males when raised on diet without tetracycline. Transgenic lines have been developed that possess a tetracycline repressible female-lethal genetic system. Ten of these lines show high female lethality at the late larval/pupal stages and three of them present dominant female lethality. Most of the lines were comparable to the wild type parental strain in several fitness parameters that are relevant to mass rearing in a production facility. Further, three lines performed well in male mating success and male competition assays, suggesting they would be sexually competitive in the field. Consequently, one transgenic line has been selected by the New World Screwworm Program for evaluation under mass rearing conditions. Conclusions We conclude that the promising characteristics of the selected sexing strains may contribute to reduce production costs for the existing eradication program and provide more efficient population suppression, which should make a genetic control program more economical in regions wereC. hominivorax remains endemic.